(3GdYHQ hGdGYJHGQs - (3YeQh Hf HMQ Hf eMHhH GdcfGfj HGdhdGA, GddjKj, CHh YKeGf, GdLGMX,J (B255 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj Sec GdSeGA HbOQJg aEfg djS HCgd GdHQ hGdJbhi Zfj Yf GdJhGYX s
(3BNQgG (B:s
(3gh bQjH HYjO, aEfg ef Lgg cGdhGVM dG jNai Ydi cd CMO hgh bdjd ef cKjQ hLRA ef cqd aCeG GdYde GdcGed aYfO GdNdGb Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HGdeYgO fSNI CNQiGfXQ GdLRA GdChd Qbe (B594 (3COHs
(3HgGeTgG HYV GdJYdjbGJ hGdJUMjMGJ hHgG fXGe GdJYbjHIs
(3hHChdgG JedjcGJ YOI CbOegG (B1068(3g` s
(3cJHgG fGSNGf s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs